Sosialisasi dan Pendampingan Pembukaan Rekening Online Bank Muamalat (MDIN) - Silviani Khursanu Putri; Agitiya Salsa Nadea; Endang Setiawati; Angguliyah Rizqi A (Jurnal Nusantara Berbakti, 2024)
In an era driven by rapid technological development, human information needs are increasingly complex, so companies must be able to provide technological information facilities to compete in business in the global market. Mobile banking is a manifestation of the progress and development of information technology in the banking sector (Dwi Mutiara Sari, 2021 ) Based on the problem formulation explained in the introduction, a community service activity was prepared with the topic "Socialization and Assistance in Opening Bank Muamalat Online Accounts (MDIN)". Students are taught about Bank Muamalat products, including opening an account via the Muamalat DIN mobile banking application. The Muamalat DIN application is a mobile banking application from Bank Muamalat that makes it easy for customers to access services anytime and anywhere. Muamalat DIN is the latest sharia mobile version from Bank Muamalat Indonesia which offers various conveniences and facilities for customers (Shafaliza Risfany, 2022). Based on the results of the dedication and discussion, we can conclude that opening an online account makes it easier for customers to open an account without having to go to a Bank Muamalat branch office and also makes it easier for customers to use Bank Muamalat services or products. The Muamalat DIN application is a mobile banking application from Bank Muamalat that makes it easy for customers to access services anytime and anywhere.